Evaluasi Implementasi Masterplan Kawasan Agropolitan Ciwidey Menggunakan Logic Models - Isnaeni Agustina; A. Artiningsih (Jurnal Wilayah dan Lingkungan, 2017)
Rural development needs to be promoted for reducing inequalities in urban and rural areas through agropolitan development program, for example. The government of Bandung District has finished Ciwidey Agropolitan Masterplan in 2007, then implemented in 2008-2012, and evaluated in 2013-2016. This study aims to evaluate the performance of the program by using logic models to describe the input, output, outcome, and impact into a diagram and then described using causality description. The findings address that the program has positive impacts on physical and social characteristics, but it has adverse effects on the economic characteristics. This study recommends a robust support from the institutions required to developing the agropolitan area.